2007
DOI: 10.1111/j.1440-6055.2007.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐enhanced pollen and lipid‐reduced flour diets and their effect on the longevity of honey bees (Apis mellifera L.)

Abstract: As eucalypt pollens contain low concentrations of lipid, enhancing pollen diets with fatty acids was hypothesised to improve honey bee longevity. Different concentrations of linoleic and oleic acid added to eucalypt pollen were trialled in small cages containing approximately 1400 bees each. Bees fed diets of redgum (Corymbia calophylla (Lindl.) Hill & Johnson, formerly Eucalyptus calophylla) pollen had the lowest mortality of 22 diets tested for 6 weeks and had life spans (50%) greater than 42 days. Linoleic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 23 publications
3
39
0
4
Order By: Relevance
“…Studies have shown that fatty acids can inhibit fatty acid synthase activity (Mersmann et al, 1973). In this experiment, successive lipase activity decreased when ALA levels increased from 0 to 6%, which is consistent with the results of previous studies (Herbert et al, 1980;Manning et al, 2007), but interestingly, when the amount of ALA continued to increase to 8 and 10%, the lipase activity increased rapidly. Currently, no reports are consistent with this finding.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Studies have shown that fatty acids can inhibit fatty acid synthase activity (Mersmann et al, 1973). In this experiment, successive lipase activity decreased when ALA levels increased from 0 to 6%, which is consistent with the results of previous studies (Herbert et al, 1980;Manning et al, 2007), but interestingly, when the amount of ALA continued to increase to 8 and 10%, the lipase activity increased rapidly. Currently, no reports are consistent with this finding.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have demonstrated that dietary fatty acid levels are closely related to honey bee longevity. A study by Manning et al (2007) found that diets high in oleic acid significantly reduced the life of bees. This finding may possibly be because the high oleic acid diet was toxic to bees, and diets high in linoleic acid also reduced the lifespan of bees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations